POTENTIAL INHIBITORY POWER OF "CURCUMA LONGA LINN." EXTRACT AGAINST CANDIDA ALBICANS FUNGUS - Solva Yuditha; Aulia Esa Rafana; Lukas Kusparmanto (Moestopo International Review on Social, Humanities, and Sciences, 2022)
Oral candidiasis is a fungal infection that often appears on the oral mucosa. These lesions are caused by the fungus Candida albicans. Candida albicans is the most common pathogenic Candida species causing fungal infections of the oral cavity. The use of antifungal drugs is the most common way of giving, but there are many side effects that can be caused. Herbal ingredients that have antifungal effects can be alternative therapies with fewer side effects, one of which is turmeric (Curcuma longa Linn.). Turmeric has various compounds that have the potential as antifungals including curcumin, flavonoids, and essential oils that work by inhibiting the growth of fungi including Candida albicans. The purpose of this literature study is to provide scientific evidence related to the potential inhibition of turmeric extract (Curcuma longa Linn.) against Candida albicans. This writing is a literature study made based on reference sources or references obtained from journals accessed through the databases of Google Scholar, Hindawi, PubMed, Scopus, DOAJ, Research Gate and textbooks. The results of the study stated that turmeric extract had an inhibitory effect on the growth of Candida albicans, the greater the concentration of turmeric extract used, the greater the inhibition caused. Turmeric also has fewer side effects than antifungal drugs.